Successful use of stereotactic navigation in posterior spinal fusion T10-S2 with bilateral iliac screw fixation in a patient with prior spinal surgeries and osteoporosis: A case report. (August 2022) - Brown, Nolan J.; Shahrestani, Shane; Kurtz, Joshua S.; Beyer, Ryan S.; Pham, Martin H.; Osorio, Joseph
Abstract: Introduction and importance: Degenerative lumbar scoliosis is a prominent cause of adult spinal deformity with an increasing prevalence as the population ages. This pathology is associated with debilitating symptoms, including radicular back pain and lower extremity claudication. Surgical realignment of the spine and restoration of sagittal imbalance can reduce low back pain. Chronic sacroiliac dysfunction commonly causes low back radicular pain. We present a complicated case where stereotactic navigation facilitated an extensive fusion and decompression procedure for adult spinal deformity in an obese patient with multiple prior surgeries for scoliosis and sacroiliac joint pathology. Case presentation: A 69-year-old, obese female with scoliosis refractory to multiple interventions presented with severe, radicular lower back pain. On examination of the right lower extremity (RLE), she had mild weakness (3/5 strength) and reduced sensation to light touch over its anterolateral aspect (dermatome L4). She was unable to perform single leg stance or tandem walk. Imaging revealed moderate mid-lumbar levoscoliosis, severe degenerative disc disease and facet hypertrophy changes in the setting of prior multilevel lumbar fusion, and consecutive nerve root impingement between L1 and L5 (worst at L3–4). DEXA scan was consistent with osteoporosis. The patient underwent lumbar laminectomy with posterior fusion of T10-ilium, transforaminal lumbar interbody fusion, osteotomy, and decompression using stereotactic navigation. The presence of SI titanium dowels from her previous SI fusion procedure posed a challenge with respect to achieving pelvic fixation. Clinical discussion: Iliac screw placement is a critical adjunctive to lumbosacral fusion, notably for prevention of pseudoarthrosis; however, patients with prior SI fusion may present a biomechanical challenge to surgeons due to obstruction of the surgical site. The O-arm neuronavigation system was successfully used to bypass this obstruction and provide sacroiliac fixation in this procedure. Conclusion: Stereotactic navigation (The O-arm Surgical Imaging System) can effectively be used to circumvent prior SI fusion in osteoporotic bone. Highlights: Stereotactic navigation circumvents prior SI fusion in osteoporotic bone. Case complexity indicates use of O-arm to obtain pelvic fixation. Stereotactic navigation associated with benefits in posterior spinal surgery.